John n. Farquhar's Perspective on Non-Christian Religions in Terms of Salvation and Missionary Approach - Alakuş, Abdullah; Işık, Ramazan (Erciyes Üniversitesi, 2021)
John N. Farquhar is a missionary who lived in the late 19th and early 20th century. Farquhar, an Englishman with Scottish origins, was involved in missionary work in India between 1891 and 1923. He aimed to find solutions to the problems faced by missionaries during his time. Especially as the classical missionary methods started to be insufficient in India and the Hindus reacted, Farquhar tried to develop new approaches. In this context, Farquhar focused on how Christianity’s relationship should be to other religions in the example of Hinduism. And he produced work on that subject. So, Farquhar systemized the fulfilment theology approach which was in the nineteenth century British missionary ideology as a new missionary attitude. For this reason, the fulfilment theology approach is attributed to Farquhar. After the 2nd Vatican Council, it is adopted the fulfilment theology understanding as an attitude towards other religions by the Catholic Church too. Thus, that new missionary understanding has become a general approach of Christians towards other religions. First of all, in this study, Farquhar's life will be briefly mentioned and then, his deal to non-Christian religions in terms of salvation will be discussed. Because the fulfilment theology understanding is associated with the salvation of non-Christian religions. Finally, the effect of the fulfilment theology approach on the Christian world will be examined

John N. Farquhar XIX. yüzyılın sonlarında ve XX. yüzyılın başlarında yaşamış olan bir misyonerdir. İskoç asıllı bir İngiliz olan Farquhar 1891 ve 1923 yılları arasında Hindistan’da misyonerlik faaliyetlerinde bulunmuştur. O, kendi döneminde misyonerlerin karşılaştıkları sorunlara çözümler üretmeyi amaçlamıştır. Özellikle klasik misyonerlik metotlarının Hindistan’da yetersiz olmaya başlaması ve Hindular tarafından tepki çekmesi sonucunda Farquhar tarafından yeni yaklaşımlar geliştirilmeye çalışılmıştır. Bu bağlamda Farquhar, Hinduizm özelinde Hıristiyanlığın diğer dinlerle ilişkisinin nasıl olması gerektiği üzerine durmuş ve bu alanda çalışmalar yapmıştır. Farquhar, yeni bir misyonerlik yöntemi olarak XIX. yüzyıl İngiliz misyonerlik düşüncesinde var olan tamamlayıcı teoloji yaklaşımını sistematikleştirmiştir. Bu nedenle tamamlayıcı teoloji yaklaşımı Farquhar ile anılır olmuştur. II. Vatikan Konsili sonrasında Katolik Kilisesi tarafından da diğer dinlere karşı bir tutum olarak tamamlayıcı teoloji anlayışı benimsenmiştir. Böylece bu yeni misyonerlik anlayışı Hıristiyanların, öteki dinlere karşı genel bir yaklaşımı haline gelmiştir. Bu çalışmada öncelikle Farquhar’ın hayatından kısaca bahsedilecek ve sonra da onun Hıristiyanlık dışındaki dinlere kurtuluş açısından bakışı ele alınacaktır. Çünkü tamamlayıcı teoloji anlayışı Hıristiyanlık dışındaki dinlerin kurtuluşu ile ilişkilendirilmektedir. Son olarak da tamamlayıcı teoloji yaklaşımının Hıristiyan dünyasına etkisi incelenmeye çalışılacaktır.
John N. Farquhar’ın Kurtuluş Açısından Hıristiyanlık Dışındaki Dinlere Bakışı ve Misyonerlik Anlayışı